Study of Path Analysis and Genetic Divergence in Some Lathyrus Genotypes in Terai Region of West Bengal - Barai, R.; Chakraborty, S.; Sarkar, A.; Mandal, R.; Chakraborty, M.; Kundu, A.; Debnath, M. K.; Sen, S. (International Journal of Bio-resource and Stress Management, 2022)
The experiments were conducted at Research cum Instructional Farm Uttar Banga Krishi Viswavidyalaya at Pundibari, Coochbehar, West Bengal, India during (2019–20 and 2020–21) for characterization and evaluation according DUS descriptors of physiological characters developed by IPGRI, Rome, Italy. Path analysis and genetic divergence of characters were made where agglomerative or bottom-up approach was made with each observation for finding out the quantitative and qualitative characters association with yield. From the path analysis of the data, days to 50% flowering, days to maturity, plant height, leaf breadth, pods per plant, pod length, pod width, seeds per plant, and seed index were found to have a direct effect on biological yield per plot at 5% and 1% level of significance. Indirect effects of all other characters in these characters were also evaluated. Selection can be done on these parameters for future breeding programme from direct observations. From the dendrogram and cluster analysis, genotypic relatedness among 10 genotypes, three groups of clusters were found. Group-I have five genotypes (Bidhan-1) BK-37-2, Kaikhali Local, Bidhan-2, Pundibari Local, and Alipurduar Local, Group-II has one genotype Berhampur Local, Group-III has four genotypes WBK-10, BK-2, BK-27-1, and BK-7-1. Here Berhampur Local was found to be very distantly related to all the genotypes. Breeding programs or crossing programs between the groups will have better future genotypes because of distantly related genotypes which will ultimately create a broad genetic base in the future lathyrus generation.